Range extension of the rare braconine genus, Lyricibracon Quicke (Hymenoptera: Braconidae), with the description of a new species from India - Ranjith, A.p.; Santhosh, S.; Nasser, M. (Zootaxa, 2017)
The extremely rare, monotypic genus Lyricibracon Quicke, previously known only from L. bicolorus Quicke in Brunei, is recorded from the Indian subcontinent for the first time through description of Lyricibracon jenningsi sp. nov. The two species are described, keyed and illustrated. The genus is a member of the Plesiobracon group of genera of the tribe Braconini.